Assessment of Lippia Citriodora Oil Effect on Sleep Disturbances in Ageing: A Double Blind Randomized Controlled Trial - Seyran Mohamadi; Robab Sahaf; Mehrdad Karimi; Ahmad Ali Akbari Kamrani; Mohsen Shati; Arash Mirabzadeh; Gholam Reza Ansari (University of Social Welfare & Rehabilitation Sciences, 2020)
Objectives: The elderly population is increasing globally and as the age increases and the functions of some organs decrease, some problems in elderly age, including sleep problems increase. Sleep disturbances cause neurological, autonomic, and biological changes. Therefore, attention should be paid to the problems that eliciting for the elderly and their families subsequently. The aim of this study was to evaluate the effect of oil on lemon on sleep disorders in the elderly. Methods & Materials: The study is a stratified design with IRCT2016061528485N1 registration Code and IR.USWR.REC.1395.50 Code of Ethics approved by the Ethics Committee of the University of Social Welfare and Rehabilitation Sciences. A total of 93 subjects (45 men and 48 women) were enrolled in the intervention, 22 men in the intervention group, 23 in the control group, 24 in the intervention group and 24 in the control group. Of these, 85 participated in the third stage of the intervention, 43 women (51%) and 42 men (49%), 41.17% in the age group of 74-60 years and 58.82% in the age group above 75 years. The Mean±SD age of the elderly was 75.88 ± 9.19 years, with the lowest age of 61 years and the highest age of 94 years. Outbreaks were hospitalized, departures and deaths. After completing an examination, a score of more than 5 Pittsburgh questionnaires, a visit by a psychiatrist and a self-reported sleep disorder, and considering the medical records, consumables , and entry criteria they were studied according to the randomization tables and divided into intervention and control groups. Validity and reliability of Pittsburgh questionnaire have been studied in various research. The intervention group received oil from the lemon and the inactive oil control group for four weeks, once daily, twice daily in the morning and night, with a drop per nose. No specific side effects were reported. In 3 cases, mild headache was reported, which was associated with a history of sinusitis, and the intervention was either performed or excluded from the tampon. Results: At the beginning of the study, demographic questionnaires, Pittsburgh Sleep Quality Index, and then Pittsburgh Questionnaire 2 and 4 weeks after the beginning of the intervention, were again asked by interview method and the data were analyzed by SPSS v. 23. The tests were one-way variance analysis, follow-up tests, independent samples  T and single-sample t-test. Conclusion: Based on the results of the study, the oil to lemon has been shown to improve the sleep disorders of the elderly in the intervention group (P 000.03) and Effect size = 0.155). Sleep disturbances The intervention group improved in the second week and the fourth week  after the onset of intervention compared to the control group